Wie Kinder mit Sprachentwicklungsstörungen das grammatische Genus im prädiktiven Sprachverstehen nutzen - Günther, Thomas; Cholewa, Jürgen (Sprache · Stimme · Gehör, 2025)
The article addresses predictive language comprehension in children with development language disorders (DLD). It shows that these children have difficulties utilizing grammatical gender cues. While healthy children do this effectively, children with SES are limited in their predictive abilities. The article emphasizes the need to develop diagnostic procedures and therapeutic interventions that promote the predictive use of grammatical knowledge.
Keywords: Sprachentwicklungsstörung; Sprachverständnis; grammatisches Genus